Fusarium Nonpatogen sebagai Agens Hayati Penyakit Rebah Kecambah pada Tanaman Terung - Ahmad Muslim (Jurnal Fitopatologi Indonesia, 2015)
Rhizoctonia solani is an important soil borne pathogen causing damping-off, stem and root rot disease. The pathogen has a wide range of hosts including eggplant. This experiment was conducted to determine the ability of  nonpathogenic isolates of Fusarium against rhizoctonia damping-off caused by R. solani in eggplant by seedling treatment. The result showed that treatment with nonpathogenic Fusarium significantly inhibited damping-off disease development. Nonpathogenic Fusarium effectively reduced disease severity, ranged from 59.02–96.72%. Treatment with nonpathogenic Fusarium was also able to increase plant height and fresh weight of eggplant seedling ranged from 40.00–60.98% and 21.80–66.53%, respectively. This results indicated that nonpathogenic Fusarium could be applied as potential biocontrol agent for damping-off disease caused by R. solani.